2022
DOI: 10.1093/bjd/ljac004
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on the lived experience of granuloma annulare

Abstract: Granuloma annulare is a relatively common inflammatory skin disease, yet patient-centered impacts of GA have not been thoroughly investigated, including the potential psychosocial and symptomatic burden, patients’ motivation for treatment, and patients’ perception of usefulness of commonly used medications. We conducted a survey of greater than 900 patients with GA and found an unexpectedly significant impact of GA on the quality of life, a generally poor reported response to commonly used therapies, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, other patients do not experience spontaneous remission (and if they do, disease can still recur). Furthermore, very little has been known about the QOL impacts of GA. Clark et al. (2023) recently found that GA may have an unexpectedly profound QOL burden in some patients, especially in those with generalized disease.…”
Section: Gamentioning
confidence: 99%
“…However, other patients do not experience spontaneous remission (and if they do, disease can still recur). Furthermore, very little has been known about the QOL impacts of GA. Clark et al. (2023) recently found that GA may have an unexpectedly profound QOL burden in some patients, especially in those with generalized disease.…”
Section: Gamentioning
confidence: 99%